Proposed Marketing Strategy for Bank MSP to Increase User and Usage of Mobile Banking - Pradipta, Mega Sylva; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2014)
Abstract.Currently, banking industry in Indonesia is so tight. Bank must have a value added and competitive advantage to attract a new customer and retain existing customer. All Banks should strive to sustain in the competition. One value added that become competitive advantage to survive in the competition is technological advance based. One kind of technology that becomes prominent for the future is Branchless Banking. Branchless Banking is needed by customers because customers want a simple banking technology that can perform so many transactions. One branchless banking is Mobile Banking that provides banking transactions through a hand phone. Current trend reflects that Handphone become must have thing for all people. However, in Bandung mobile banking face problems so that Bank Ã¢â‚¬Å“MSPÃ¢â‚¬Â cannot significantly increase user and usage of mobile banking. Based on internal and external analysis there are some deficiencies for Bank Ã¢â‚¬Å“MSPÃ¢â‚¬Â to increase user ad usage of Mobile Banking. Based on surveys and observations conducted, high sales target, incentives/bonus/reward considerations and unclear target market are internal problems that facing customer service as the main responsible person that should sell mobile banking. Lack promotion, many subtitutes product, unflexible promotion tools, no name corelation with brand, not interesting of promotion display & content and customer service that not helpful are the external problems of mobile banking. Some alternatif solutions that can be used was considered. Changing product name is considered to solve brand name problems that not familiar, hire outsourcing people as salesperson also being considered in order to solve internal problems for customer service that has selling product orientation because of high sales target, incentives/bonus/reward considerations and external side to help customers find out more deeply about mobile banking. Bank Ã¢â‚¬Å“MSPÃ¢â‚¬Â also must know their target market precisely by increasing awareness and interest. The other way to cover awareness and interest are set of promotion that contains local media and using popular social media in Bandung, in banking promotion, brochures, special promotion likes point reward, member get member, discount for shopping and special event. The special feature of Mobile Banking also should maximize in order to become point of sales. In addition bundling registration with Internet Banking and display demo mobile banking product also should launch to grab a new user and retain existing user of mobile banking.Ã‚Â The implementation of marketing strategy will take one year ahead and starting at July 2014 until June 2015. To support this marketing strategy budget will require for around IDR 259,100,000.Keywords: Marketing Mix, Consumer Behavior, Mobile Banking, Awareness, Interest